Peran Lembaga Keuangan Internasional dalam Pembiayaan Proyek Infrastruktur di Negara Berkembang - Sangfitri, Selfi (Universitas Pahlawan Tuanku Tambusai, 2025)
Infrastructure development in developing countries brings new challenges and opportunities to realize sustainable infrastructure interconnection. In the face of this uncertainty, sustainable infrastructure development is essential to support economic growth and address the country's future challenges. This study uses a literature review method to detail and understand various aspects of sustainable infrastructure development in developing countries. The formulation of the research problem is the role of international financial institutions in infrastructure projects in developing countries. In his analysis, the researcher discusses the importance of the concept of sustainable infrastructure, which not only includes durable physical development, but also the integration of social, economic, and environmental aspects. In the era of continuous global development, sustainable infrastructure is the main focus in supporting economic growth without neglecting the sustainability of the natural ecosystem. Discussion on the opportunities for developing countries in handling infrastructure development, improving transportation infrastructure, and improving other infrastructure. However, there are several challenges that must be overcome, such as financial limitations, differences between developing countries in terms of infrastructure, environmental aspects, and the role of the private sector in infrastructure investment and management. This study is expected to provide a comprehensive view of the efforts needed to achieve sustainable infrastructure development in developing countries.